Honorary Authorship: Is There Any Chance to Stop It? Analysis of the Literature and a Personal Opinion - Emilio Quaia; Filippo Crimi’ (Tomography, 2021)
Honorary authorship corresponds to the intentional misrepresentation of credit to an individual whose contributions to a biomedical article do not meet the criteria for authorship established by the International Committee of Medical Journal Editors (ICMJE) [...]